Observation of Clinicopathologic Features of Pituitary Adenoma With Neuronal Differentiation - Zheng, Limei; Yan, Xiaorong; Hu, Chengcong; Zhang, Peng; Chen, Yupeng; Zheng, Qiaoyan; Hu, Liwen; Wang, Mi; Li, Guoping; Wu, Ping; Jiang, Changzhen; Tian, Jing; et al. (Frontiers in Endocrinology, 2022)
Objective: To investigate the clinicopathologic features of pituitary adenoma with neuronal differentiation. Methods: Four patients with mixed gangliocytoma-pituitary adenomas and 111 new-onset patients with adenomas were included in the study. The histological and immunohistochemical findings were analyzed. Neuronal differentiation marker staining was performed on new-onset adenomas, and the related literature was reviewed. Results: Altogether, more than 100 mixed gangliocytoma-pituitary adenoma cases have been reported in the literature until now, of which pituitary-specific POU-class homeodomain transcription 1 (PIT1) positive adenomas are more frequently observed. In the present study, all 4 patients we described were female, aged 29 to 53 years (mean 39 years). Clinically, 3/4 patients presented with acromegaly, and 1/2 patients presented with headache. Histologically, the tumor was composed of two distinct mixed components. The one was a population of neoplastic ganglionic cells with large nuclei, prominent nucleoli, and abundant basophilic cytoplasm embedded in a fibrillary background. Stains of chromograninA (CgA), synaptophysin (Syn), Calretinin (CR) were positive. Axotomy-like expression was observed in neurofilament (NF) staining. PIT1 was expressed in partial ganglionic cells in all cases. The other component was a population of small uniform cells with round nuclei and acidophilic cytoplasm. Prolactin (PRL) and growth hormone (GH) were positive in all 4 cases. PIT1 was positive in the nuclei of adenomas. Although adenomas and ganglionic regions varied in histology, there was a population of cells with neuronal differentiation expressing PIT1. Additionally, axotomy-like expression of NF staining could be seen in a distant area of adenoma regions. A total of 111 cases of adenomas without ganglionic cells were included in this study, including 7 cases with neuronal differentiation. Among them, 4 cases were prolactinomas, 2 cases were somatotroph adenomas, and 1 case was corticotroph adenoma. Interestingly, all cases but one were PIT1-positive adenomas. Conclusions: Mixed gangliocytoma-pituitary adenomas are rare tumors with neuronal differentiation. The majority of MGAs are associated with endocrinopathies. Our results suggest that PIT1-positive pituitary adenomas may have neural differentiation potential, which may not be unusual. This indication supports the possibility that the neuronal transdifferentiation of adenomatous cells is a possible mechanism, and the underlying mechanism requires further elucidation.